2020
DOI: 10.1021/acsphotonics.0c01079
|View full text |Cite
|
Sign up to set email alerts
|

Indium Tin Oxide Nanoparticle-Coated Silica Microsphere with Large Optical Nonlinearity and High Quality Factor

Abstract: High nonlinearity optical devices are of interest for compact, low power devices. Whispering gallery mode (WGM) microresonators offer strong nonlinear optical responses due to high quality factors and the small mode volume. To achieve high nonlinearity with these WGM devices, both a material with a high nonlinear index as well as a high quality factor is required. Indium tin oxide (ITO) is an excellent nonlinear material due to an exceptionally high nonlinear refractive index found at the epsilon-near-zero wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Depending on the dimensions and specific features of studied small-sized structures, Mie resonance can appear in a broad spectral range (from the deep UV up to the near-IR wavelength region). Regarding the samples examined in the present work, we would like to refer to the study of Bae et al [ 16 ], which has shown that the absorption spectrum of the small-sized aggregates of ITO was notably modified once they considered the species of different sizes compared with the films contained the molecules of ITO. This difference was manifested in the IR range, which showed significant growth of absorbance of the ITO nanoparticle suspensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the dimensions and specific features of studied small-sized structures, Mie resonance can appear in a broad spectral range (from the deep UV up to the near-IR wavelength region). Regarding the samples examined in the present work, we would like to refer to the study of Bae et al [ 16 ], which has shown that the absorption spectrum of the small-sized aggregates of ITO was notably modified once they considered the species of different sizes compared with the films contained the molecules of ITO. This difference was manifested in the IR range, which showed significant growth of absorbance of the ITO nanoparticle suspensions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other studies, these QDs showed larger absorption in the near-infrared region (i.e., at the wavelengths above 800 nm). Previous studies have shown that by decreasing the size of ITO QDs, the absorption band shifts closer to the visible range [ 16 ]. For example, the 9 nm ITO NPs showed an absorption maximum of around 1600 nm compared to the 30 nm NPs that had an absorption maximum at 2000 nm.…”
Section: Description Of Samples and Methods Of Measurementsmentioning
confidence: 99%
“…5,6 ITO nanoparticles manifest large optical nonlinearity due to the field enhancement at the surface plasmon resonance (SPR) frequencies. 7 Infrared photocurrent driven by plasmonic photoconduction was observed in ligand-free ITO nanoparticle films, demonstrating their potential for next generation infrared optoelectronic technologies. 8 In addition, ITO nanoparticles also exhibit intrinsic bandgap absorption in the UV band, which can be applied for the preparation of dualband photodetectors in UV and IR regions.…”
Section: Introductionmentioning
confidence: 96%
“…Reverse-saturable absorbers and materials with two- and multi-photon absorptions are also used as optical limiters and in nonlinear microscopy, 3D imaging, and nonlinear spectroscopy [ 29 ]. In order to design and develop more efficient NLO devices, great attention has turned to find materials with larger NLO response in recent years [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%